Influence of Incoming Plate Relief on Overriding Plate Deformation and Earthquake Nucleation: Cocos Ridge Subduction (Costa Rica). Issue 12 (18th December 2019) - Martínez‐Loriente, Sara; Sallarès, Valentí; R. Ranero, César; B. Ruh, Jonas; Barckhausen, Udo; Grevemeyer, Ingo; Bangs, Nathan
Abstract: We present a 2‐D P wave velocity model and a coincident multichannel seismic reflection profile characterizing the structure of the southern Costa Rica margin and incoming Cocos Ridge. The seismic profiles image the ocean and overriding plates from the trench across the entire offshore margin, including the structures involved in the 2002 Osa earthquake. The overriding plate consists of three domains: Domain I displays thin‐skinned deformation of an imbricate thrust system composed of fractured rocks. Domain II shows ~15‐km‐long landward dipping reflection packages and active deformation of the shelf sediment. Domain III is little fractured and appears to be dominated by elastic deformation, overlain by ~2‐km‐thick landward dipping strata. The velocity structure supports the argument that the bulk of the margin is highly consolidated rock. Thick‐skinned tectonics probably causes the uplift of Domains II and III. The oceanic plate shows crustal thickness variations from ~14 km at the trench (Cocos Ridge) to 6–7 km beneath the shelf. We combine (1) interplate geometry and fracturing degree, (2) tectonic stresses and brittle strain, and (3) earthquake locations, to investigate relationships between structure and earthquake generation. The 2002 Osa sequence nucleated at the leading flank of subducting seamounts in the area of highest tectonic overpressure. Both estimated rock fracturing and modeled brittle strain steadily increase from the leading flank of the subducting seamounts to their top, reflecting the progressive damage caused by the seamount. Therefore, the seismicity and structural‐mechanical evolution of the upper plate reflect the downward propagation of the leading edge of seamounts. Key Points: Costa Rica Osa margin has three across‐strike domains based on structural and physical properties The bulk of the margin is consolidated rock, fronted by a 20‐ to 30‐km‐wide accreted prism Subducting seamounts correlate with upper‐plate strain, overpressure, and earthquakes